Relative Risk Analysis of Patient Return Within 72 Hours to Emergency Department - Aishwarya TR; Naveen Kumar P (Online Journal of Health & Allied Sciences, 2022)
Introduction: Transparency in patient care in an emergency department can be projected by capturing data from the medical records of patients. Policy makers envision that transparency in this data will allow the patient to choose the right hospital of his choice. Relative risk is a ratio of the probability of an event occurring in the exposed group versus the probability of the event occurring in the non-exposed group. It is usually used in the scenario of clinical events. In this study we have used it to analyse one of the key performance indicators used in Emergency Department, as per Emerald standards. The problem statement identified in the study is the returning of patients to the Emergency department of a private, tertiary care hospital within 72 hours after the initial visit. A revisit in this study is assumed as an unplanned visit done by the patient within 72 hours with similar presenting complaints. Methodology: A retrospective cohort study for all emergency visits between January to June 2021. People who returned to EMD within 72 hours were compared to other non-re attending patients based on medical diagnosis, patient demographics, mode of arrival, triage category and qualification of doctors in charge. Multivariate analysis using the generalized linear model was conducted on variables associated with 72-hour ED re-attendance. Result: Among 18,355 patients, 128 (0.69%) were in the 72-hour re-attendees’ group. Multivariate analysis showed female gender as more, above 60 years of age, arrival by ambulance, triaged as yellow. Among the ICD-10 diagnosis for the patients who returned, it was not possible to identify one specific condition. But abdominal pain was one reason for the re-visit of a few patients. There was also a significant difference in the seniority ranking of the doctor-in-charge between both groups. Conclusion: Identification of characteristics of patients lead to improved care by surgeons and gastroenterology.